Fighting the polar ice, by Anthony Fiala, commander of the Ziegler Polar Expedition . with an introduction by W. S. Champ, and reports by William J. Peters, Russell W. Porter and Oliver S. Fassig. Illustrations from photographs and sketches by the author. Also nine, from paintings in colour by Russell W. Porter and J. Knowles Hare. - Fiala, Anthony, 1869-1950. (New York, Doubleday, Page & Co., 1906)
xxii, 296, [6] p.